Pregunta
upstudy study bank question image url

QUESTION 7 7.1 Determine \( f^{\prime}(x) \) from first principles if \( f(x)=\frac{1}{x} \). 7.2 Determine: 7.2.1 \( \frac{d}{d x}\left(\sqrt{4 x^{6}}+\sqrt{2} \cdot x^{2}\right) \) 7.2.2 \( g^{\prime}(x) \) if \( g(x)=\frac{3 x^{4}-4 x^{2}+6}{x^{2}} \) (3) 7.3 The equation of the tangent to \( f(x)=3 x^{2}+b x+c \) at \( x=1 \) is given by \( y=9 x-9 \). Determine the values of \( b \) and \( c \). (4) [15]

Ask by Mills Kelly. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

7.1. \( f'(x) = -\frac{1}{x^2} \) 7.2.1. \( \frac{d}{dx} \left( \sqrt{4x^6} + \sqrt{2} \cdot x^2 \right) = 6x^2 + 2\sqrt{2}x \) (for \( x \geq 0 \)) 7.2.2. \( g'(x) = 6x - \frac{12}{x^3} \) 7.3. \( b = 3 \) and \( c = -6 \)

Solución

Below is the full solution with step‐by‐step reasoning. ───────────────────────────── Problem 7.1 ───────────────────────────── We wish to find f′(x) from first principles for   f(x) = 1/x. Using the definition of the derivative:   f′(x) = lim₍ₕ→0₎ [f(x + h) − f(x)] / h Step 1. Write the difference quotient:   f′(x) = lim₍ₕ→0₎ [(1/(x + h) − 1/x) / h]. Step 2. Combine the fractions inside the bracket:   1/(x+h) − 1/x = (x − (x+h)) / [x(x+h)] = −h / [x(x+h)]. Thus,   f′(x) = lim₍ₕ→0₎ [ (−h / (x(x+h))) / h ]. Step 3. Cancel h (as long as h ≠ 0):   f′(x) = lim₍ₕ→0₎ [−1 / (x(x+h))]. Step 4. Take the limit as h → 0:   f′(x) = −1 / (x·x) = −1/x². ───────────────────────────── Problem 7.2.1 ───────────────────────────── Determine the derivative of   f(x) = √(4x⁶) + √2 · x². Step 1. Rewrite √(4x⁶):   √(4x⁶) = √4 · √(x⁶) = 2|x³|. For many problems, the domain is assumed to be x ≥ 0 so that |x³| = x³. (If x can be negative, you must account for the absolute value; here we assume x ≥ 0.) Thus, assume x ≥ 0 and get:   f(x) = 2x³ + √2 · x². Step 2. Differentiate term-by-term:   d/dx (2x³) = 6x²,   d/dx (√2 · x²) = 2√2 x. The derivative is:   f′(x) = 6x² + 2√2 x. ───────────────────────────── Problem 7.2.2 ───────────────────────────── Find g′(x) for   g(x) = (3x⁴ − 4x² + 6) / x². Step 1. Divide each term in the numerator by x²:   g(x) = 3x² − 4 + 6/x². Step 2. Differentiate term-by-term:   d/dx (3x²) = 6x,   d/dx (−4) = 0,   d/dx (6/x²) = 6 · d/dx (x^(−2)) = 6(−2)x^(−3) = −12/x³. Thus,   g′(x) = 6x − 12/x³. ───────────────────────────── Problem 7.3 ───────────────────────────── The function is   f(x) = 3x² + bx + c, and the equation of the tangent at x = 1 is given as   y = 9x − 9. The tangent line must satisfy two conditions at x = 1: 1. It must pass through the point (1, f(1)). 2. Its slope must equal f′(1). Step 1: Use the point of tangency.   f(1) = 3(1)² + b(1) + c = 3 + b + c. The tangent line at x = 1 gives y = 9(1) − 9 = 0. Thus,   3 + b + c = 0  →  b + c = −3.                  (Equation 1) Step 2: Use the slope.   f′(x) = derivative of 3x² + bx + c = 6x + b. Then, at x = 1:   f′(1) = 6 + b. Since the slope of the tangent is 9, we have:   6 + b = 9  →  b = 3. Step 3: Substitute b = 3 into Equation 1:   3 + c = −3  →  c = −6. ───────────────────────────── Final Answers Summary ───────────────────────────── 7.1   f′(x) = −1/x². 7.2.1  d/dx [√(4x⁶) + √2·x²] = 6x² + 2√2 x      (for x ≥ 0). 7.2.2  g′(x) = 6x − 12/x³. 7.3   For f(x) = 3x² + bx + c with tangent y = 9x − 9 at x = 1, we have b = 3 and c = −6.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To find \( f^{\prime}(x) \) from first principles for \( f(x)=\frac{1}{x} \), we start with the definition of the derivative: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{f(x+h) - f(x)}{h} = \lim_{h \to 0} \frac{\frac{1}{x+h} - \frac{1}{x}}{h} = \lim_{h \to 0} \frac{x - (x+h)}{h \cdot x(x+h)} = \lim_{h \to 0} \frac{-h}{h \cdot x(x+h)}. \] This simplifies to: \[ f^{\prime}(x) = \lim_{h \to 0} \frac{-1}{x(x+h)} = -\frac{1}{x^2}. \] In resolving \( \frac{d}{d x}\left(\sqrt{4 x^{6}}+\sqrt{2} \cdot x^{2}\right) \), we first simplify: \[ \sqrt{4 x^6} = 2x^{3}, \text{ so } f(x) = 2x^{3} + \sqrt{2}x^{2}. \] Now, using the power rule, we differentiate: \[ \frac{d}{dx}(2x^{3}) = 6x^{2}, \quad \frac{d}{dx}(\sqrt{2}x^{2}) = 2\sqrt{2}x. \] So, \[ \frac{d}{dx}\left(\sqrt{4x^{6}}+\sqrt{2} \cdot x^{2}\right) = 6x^{2} + 2\sqrt{2}x. \] For \( g^{\prime}(x) \) where \( g(x) = \frac{3x^4 - 4x^2 + 6}{x^2} \), we can use the quotient rule: \[ g^{\prime}(x) = \frac{(12x^3 - 8x)(x^{2}) - (3x^4 - 4x^2 + 6)(2x)}{(x^2)^2}. \] Simplifying gives: \[ g^{\prime}(x) = \frac{12x^5 - 8x^3 - 6x^2 + 8x^2 - 12x^4 + 8}{x^4} = \frac{(12x^5 - 12x^4) + 8 - 6x^2}{x^4}. \] Moving to the next point, for the tangent line to \( f(x) = 3x^{2} + b x + c \) at \( x = 1 \) being \( y = 9x - 9 \), we know the slope (derivative) at that point must equal 9: \[ f'(x) = 6 + b = 9 \implies b = 3. \] Now substituting \( x = 1 \): \[ f(1) = 3(1^2) + 3(1) + c = 6 + c = -9 \implies c = -15. \] Thus, \( b = 3 \) and \( c = -15 \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad